Baseline Hemoglobin, Hepcidin, Ferritin, and Total Body Iron Stores are Equally Strong Diagnostic Predictors of a Hemoglobin Response to 12 Weeks of Daily Iron Supplementation in Cambodian Women. Issue 8 (12th May 2021) - Pei, Lulu X; Kroeun, Hou; Vercauteren, Suzanne M; Barr, Susan I; Green, Tim J; Albert, Arianne Y; Karakochuk, Crystal D
ABSTRACT: Background: The WHO recommends daily iron supplementation for all women in areas where the population-level anemia prevalence is ≥40%, despite the fact that hemoglobin (Hb) concentration is generally considered to be a poor prognostic indicator of iron status. Objectives: In this secondary analysis, we investigated the predictive power of ten baseline hematological biomarkers towards a 12-week Hb response to iron supplementation. Methods: Data were obtained from a randomized controlled trial of daily iron supplementation in 407 nonpregnant Cambodian women (18–45 years) who received 60 mg elemental iron as ferrous sulfate for 12 weeks. Ten baseline biomarkers were included: Hb, measured with both a hematology analyzer and a HemoCue; inflammation-adjusted ferritin; soluble transferrin receptor; reticulocyte Hb; hepcidin; mean corpuscular volume; inflammation-adjusted total body iron stores (TBIS); total iron binding capacity; and transferrin saturation. Receiver operating characteristic (ROC) curves from fitted logistic regression models were used to make discrimination comparisons and variable selection methods were used to construct a multibiomarker prognostic model. Results: Only 25% ( n  = 95/383) of women who completed the trial experienced a 12-week Hb response ≥10 g/L. The strongest univariate predictors of a Hb response were Hb as measured with a hematology analyzer, inflammation-adjusted ferritin, hepcidin, and inflammation-adjusted TBIS (AUC ROC  = 0.81, 0.83, 0.82, and 0.82, respectively), and the optimal cutoffs to identify women who were likely to experience a Hb response were 117 g/L, 17.3 μg/L, 1.98 nmol/L, and 1.95 mg/kg, respectively. Hb as measured with a hematology analyzer, inflammation-adjusted ferritin, and hepcidin had the best combined predictive ability (AUC ROC =0.86). Hb measured with the HemoCue had poor discrimination ability (AUC ROC  = 0.65). Conclusions: Baseline Hb as measured with a hematology analyzer was as strong a predictor of Hb response to iron supplementation as inflammation-adjusted ferritin, hepcidin, and inflammation-adjusted TBIS. This is positive given that the WHO currently uses the population-level anemia prevalence to guide recommendations for untargeted iron supplementation.